Protein kinase B and extracellular signal‐regulated kinase contribute to the chondroprotective effect of morroniside on osteoarthritis chondrocytes. Issue 8 (5th March 2015) - Cheng, Liang; Zeng, Guoqing; Liu, Zejun; Zhang, Bing; Cui, Xu; Zhao, Honghai; Zheng, Xinpeng; Song, Gang; Kang, Jian; Xia, Chun
Abstract Despite extensive studies on the multifaceted roles of morroniside, the main active constituent of iridoid glycoside from Corni Fructus, the effect of morroniside on osteoarthritis (OA) chondrocytes remains poorly understood. Here, we investigated the influence of morroniside on cultured human OA chondrocytes and a rat experimental model of OA. The results showed that morroniside enhanced the cell viability and the levels of proliferating cell nuclear antigen expression (PCNA), type II collagen and aggrecan in human OA chondrocytes, indicating that morroniside promoted chondrocyte survival and matrix synthesis. Furthermore, different doses of morroniside activated protein kinase B (AKT) and extracellular signal‐regulated kinase (ERK) in human OA chondrocytes, and in turn, triggered AKT/S6 and ERK/P70S6K/S6 pathway, respectively. The PI3K/AKT inhibitor LY294002 or the MEK/ERK inhibitor U0126 attenuated the effect of morroniside on human OA chondrocytes, indicating that the activation of AKT and ERK contributed to the regulation of morroniside in human OA chondrocytes. In addition, the intra‐articular injection of morroniside elevated the level of proteoglycans in cartilage matrix and the thickness of articular cartilage in a rat experimental model of OA, with the increase of AKT and ERK activation. As a consequence, morroniside has chondroprotective effect on OA chondrocytes, and may have the therapeutic potential for OA treatment.